How Adolescents with Diabetes Experience Social Support from Friends: Two Qualitative Studies - Louk W. H. Peters; Laura Nawijn; Nicole M. C. van Kesteren (Scientifica)
Self-management of diabetes is challenging, especially for adolescents who face multiple changes, including closer peer relationships. Few studies have explored how friends can provide constructive support in this effort. The present research investigated, in two qualitative studies, the perceptions of adolescents with diabetes and their friends with respect to the positive social support that friends can offer. In study 1, 28 adolescents aged 12–15 with type 1 diabetes participated in online focus groups. In study 2, 11 of these adolescents were interviewed in person together with their best friends. The data were analysed by means of content analysis. In study 1, the adolescents with diabetes identified various supportive behaviours of friends, particularly concerning emotional support: treating them normally, showing interest, having fun, providing a distraction, and taking their diabetes into account. They differed in their attitude towards support, and this influenced which behaviours they perceived as supportive. Study 2 showed that the adolescents with diabetes and their friends often had similar opinions on the desired degree of support. Fear of stigmatization and sense of autonomy withheld some adolescents with diabetes from soliciting more support. These insights can be useful in patient education aiming to promote social support.